The average of all my grades is x + 0.35(don't judge).X is 2 ( b ( − 1 ) + 6 ) + 2 ( b ( − 1 ) + 5 ) + 2 ( b ( − 1 ) + 1 ) where b ( t ) = g ( t ) − e ∗ f ( e ) where g ( x ) ( D ∗ f ( x ) + C ∗ ∫ f ( x ) d x + B ∗ ∫ ∫ f ( x ) d x d x ) is the solution to y ′ ′ ′ + 3 y ′ ′ + 3 y ′ + y = 0 . Find x.B and C are constants of integration.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
.The hard part of the problem is solving for the solution of the differential equation above.We can factor the equation as y(D+I)^3 = 0 .Rewrite the equation as z'+z=0 where z is y(D+I)^2.By basically common sense the solution is e^-t.Now set e^-t=y(D+I)^2.Rewrite as e^-t = n'+n.Multiply by e^t and you have a product loop y'e^t+ye^t.Integrate and you have ye^t = t+B and multiply out by e^-t.So te^-t +Be^-t = y'+y.Repeating the technique shown earlier we have e^-t(t^2/2+Bt+C)(note that the constants of integration are reversed in the problem).Plugging in e^-t as g(t) we have e -e^f(e).f(e)=1 so e-e=0.x= 2^6+2^5+2^1 = 98 the answer.98.35? terrible!